2008
DOI: 10.2298/gsf0897127d
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effect of quality factors on the assortment structure in poplar plantations

Abstract: Quality factors affecting the assortment quality structure in poplar plantations were researched on nine temporary sample plots in the period 1997-2004, from the aspect of the implementation of roundwood standards. Sample plots were selected depending on the factors, the effect of which was studied. The following factors were researched: clonal species, planting pattern, flood risk, pruning of branches, plantation position and age. The study was performed by the original methodology. Based on the study results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In middleaged stands, future timber production is improved by thinning treatments that influence the growth of individual trees (Pretzsch 2009). Several authors (Danilović 2008;Prka & Krpan 2010) have shown thinning may greatly improve final timber quality, as this changes the final habitus of individual trees, which improves log quality for a given tree (Prka 2012). In addition, species diversity may help increase forest productivity by promoting denser and more structurally complex canopies (Jucker et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In middleaged stands, future timber production is improved by thinning treatments that influence the growth of individual trees (Pretzsch 2009). Several authors (Danilović 2008;Prka & Krpan 2010) have shown thinning may greatly improve final timber quality, as this changes the final habitus of individual trees, which improves log quality for a given tree (Prka 2012). In addition, species diversity may help increase forest productivity by promoting denser and more structurally complex canopies (Jucker et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Stand assortment structure is influenced by a number of factors (Danilović 2008;Prka & Krpan 2010;Prka 2012). One of the main factors affecting the distribution of timber assortments in individual trees is the diversity of tree habitus (stem and crown shape; Prka 2012), which is largely influenced by forest structure.…”
Section: Introductionmentioning
confidence: 99%
“…Stand assortment structure is influenced by a combination of several factors including site conditions (Danilović 2006), silvicultural measures (Danilović 2008;Prka, Krpan 2010), stand density, spatial distribution of trees, species composition (Liang et al 2007), and diversity of tree habitus (Prka 2012). The results of our analysis confirmed that the quality of timber production is a result of multiple relations because the explanatory power of the univariate linear regressions was low (the average significant correlation coefficients did not exceed 0.7, Fig.…”
Section: Discussionmentioning
confidence: 99%